Respuesta:
a) 25
Explicación paso a paso:
n(A u B) - n(A Δ B) = n(A n B)
18 - 13 = n(A n B)
n(A n B) = 5
n(A - B) + n(A n B) = n(A)
7 + 5 = n(A)
n(A) = 12
n(A u B) - n(A n B) + n(A) = n(A) + n(B)
n(A) + n(B) = 18 - 5 + 12
n(A) + n(B) = 25
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Verified answer
Respuesta:
a) 25
Explicación paso a paso:
n(A u B) - n(A Δ B) = n(A n B)
18 - 13 = n(A n B)
n(A n B) = 5
n(A - B) + n(A n B) = n(A)
7 + 5 = n(A)
n(A) = 12
n(A u B) - n(A n B) + n(A) = n(A) + n(B)
n(A) + n(B) = 18 - 5 + 12
n(A) + n(B) = 25